Synthetic oligonucleotide tails inhibit in vitro and in vivo translation of SP6 transcripts of maize zein cDNA clones. - Galili, G (1986)
A maize zein cDNA clone was used to synthesize mRNA with the SP6 in vitro transcription system. Although we obtained full-length transcripts of the cDNA sequence, these were inefficient templates for protein synthesis. Removal of the 5' oligo(G) sequence that was synthesized during the cDNA cloning procedure allowed efficient translation of the mRNAs in a wheat germ cell-free protein synthesis system or in Xenopus laevis oocytes. The alteration in translational efficiency did not result from an interaction of the 5' oligo(G) homopolymer tail with the 3' oligo(C) sequence, as transcripts with or without the oligo(C) tail were translated similarly in both protein synthesis systems. Ribosome interaction with the mRNA may be affected due either to the secondary structure of the oligo(G) sequence itself, or an unusual secondary structure between the oligo(G) sequence and another region in the mRNA. Synthetic oligonucleotides at the 5' end of cloned cDNA sequences may generally be inhibitory for translation of mRNAs transcribed in vitro.